Lifetime Prevalence of Sexual Violence and Its Associated Factors among High School Female Students in Jarso District, Oromia Region, Eastern Ethiopia. (27th December 2021) - Dufera, Fufa; Kebira, Jemal Yusuf; Gobena, Tesfaye; Assefa, Nega
Abstract : Background. Sexual violence is a serious public health problem affecting millions of young girls and women across the world. Recently, the issue of sexual violence against schoolgirls has garnered global and national attention with implications for health and education outcomes. Sexual violence is driven by a multitude of risk factors that occur at different levels. Understanding the magnitude, risk factors, and conceptuality of sexual violence is crucial for setting priorities and elimination efforts at different levels. Therefore, the objective of this study was to determine the lifetime prevalence of sexual violence and associated factors among high school female students in Jarso district, Oromia region, eastern Ethiopia. Methods. A school-based cross-sectional study was conducted in public high schools of Jarso district, eastern Ethiopia, from 1 st March to 5 th April 2019. A multistage sampling technique was used to select 559 eligible study participants. Data were collected by a structured self-administered questionnaire. The outcome measure of interest was lifetime sexual violence. Bivariate and multivariable logistic regression analyses were done. Statistically significant association of variables had been declared based on the adjusted odds ratio (AOR) with its 95% CI and p value < 0.05. Results . The overall magnitude of sexual violence among female students was 28.6% (95% CI: 25%-32.2%) in the study area. Forty (7.2%) participants have experienced coercive sex against their consent. Participant's level of education ((AOR = 1.5, 95% CI (1.03–2.30)), being unmarried ((AOR = 2.80, 95% CI (1.40–5.81)), consumption of alcohol ((AOR = 3.41, 95% CI (1.11–10.40)), using substances (hashish and/or shisha) ((AOR = 2.6, 95% CI (1.02–6.50)), and ever initiated sexual intercourse ((AOR = 5.9, 95% CI (3.3–10.7)) were positively and statistically associated with sexual violence at p value < 0.05. Conclusion. The overall magnitude of sexual violence was relatively high (28.6%). Thus, any intervention aimed to address sexual violence should consider the identified associated risk factors in the study area.